Radiologist preferences for faculty development initiatives to improve resident feedback in the era of competency-based medical education - Laura Wong; Ethan Sacoransky; Wilma Hopman; Omar Islam; Andrew D. Chung; Benjamin Y. M. Kwan (Medical Education Online)
Introduction Since 2022, all Canadian post-graduate medical programs have transitioned to a Competence by Design (CBD) model within a Competency-Based Medical Education (CBME) framework. The CBME model emphasized more frequent, formative assessment of residents to evaluate their progress towards predefined competencies in comparison to traditional medical education models. Faculty members therefore have increased responsibility for providing assessments to residents on a more regular basis, which has associated challenges. Our study explores faculty assessment behaviours within the CBD framework and assesses their openness to opportunities aimed at improving the quality of written feedback. Specifically, we explore faculty’s receptiveness to routine metric performance reports that offer comprehensive feedback on their assessment patterns.Methods Online surveys were distributed to all 28 radiology faculty at Queen’s University. Data were collected on demographics, feedback practices, motivations for improving the teacher-learner feedback exchange, and openness to metric performance reports and quality improvement measures. Following descriptive statistics, unpaired t-tests and one-way analysis of variance were conducted to compare groups based on experience and subspecialty.Results The response rate was 89% (25/28 faculty). 56% of faculty were likely to complete evaluations after working with a resident. Regarding the degree to which faculty felt written feedback is important, 62% found it at least moderately important. A majority (67%) believed that performance reports could influence their evaluation approach, with volume of written feedback being the most likely to change. Faculty expressed interest in feedback-focused development opportunities (67%), favouring Grand Rounds and workshops.Conclusion Assessment of preceptor perceptions reveals that faculty recognize the importance of offering high-quality written feedback to learners. Faculty openness to quality improvement interventions for curricular reform relies on having sufficient time, knowledge, and skills for effective assessments. This suggests that integrating routine performance metrics into faculty assessments could serve as a catalyst for enhancing future feedback quality.